سياسة الإغراق وسبل دعم وحماية الإنتاج المحلي - تطبيقات مختارة مع التركيز على العراق- - نغم حسین نعمة (مجلة الغري للعلوم الاقتصادية والادارية)
الملخص إن سیاسة اغ ا رق الاسواق المحلیة بالمنتجات المستوردة والتي تزداد بشكل مضطرد سنویا منذ العام ٢٠٠٣ وحتى الان دون تدخل فاعل او وضع قوانین تنظم عملیات الادخال للبضائع التي لا تجد من یردعها او یخضعها الى ادنى درجة معمول بها من قوانین الفحص والتقییس والسیطرة النوعیة التي كان الع ا رق اصلا یتعامل بالحد الادنى معها قبل عام ٢٠٠٣ ، امتدت لتصبح دائمیة بعد ان كان یتوقع لها ان تصبح حادثا عرضیا یمتد لفترة زمنیة محددة، امست مع مرور الوقت معضلة تتطلب حلولاً جذریة. إذ بالرغم من جمیع الصعوبات التي دأب اصحاب المعامل التعامل معها والتعایش مع اثارها فضلا عن قلة الارباح المتحققة من المنتج المصنع محلیا الذي بالكاد یجد له طلبا في الاسواق من بعض الزبائن الذین لا ی ا زلون یثقون بالمنتجات الع ا رقیة ویقتنوها بین الحین والحین، فأن ظاهرة الاغ ا رق السلعي اسهمت بعض الظروف في استفحالها بشكل كبیر، منها قلة الدعم الحكومي للصناعة الوطنیة بسبب الاتجاهات المعلنة في التوجه نحو اقتصادیات السوق وخصخصة القطاع الحكومي وبشكل غیر مدروس ومخطط ومن دون المرور بمرحلة انتقالیة ولفترة زمنیة محددة عبر التوجه من الاقتصاد الذي یعتمد على الحكومة الى الاقتصاد المنفتح على نظام السوق والقطاع الخاص. إن سیاسة الاغ ا رق السلعي ظاهرة ذات ابعاد خطیرة على الاقتصاد الع ا رقي لعدة اسباب منها ان السلع الردیئة والرخیصة تخرج السلع الجیدة من المنافسة في السوق المحلیة. لذلك یتوجب ان تتصدر مهام الدولة حالیا، خطط وب ا رمج عمل قصیرة وطویلة الامد للحد منها عبر تفعیل دور التقییس والسیطرة النوعیة واستی ا رد اجهزة حدیثة متخصصة بالفحص على السلع المستوردة واختیار ملاكات كفوءة للعمل علیها، واللجوء الى سن قوانین وتشریعات تحد من ظاهرة الاغ ا رق السلعي وتنظیم عملیات الاستی ا رد والتصدیر، علاوة على ضرورة دعم الصناعة الوطنیة من خلال تشجیع الدولة للمؤسسات والشركات والقیام بش ا رء سلعها ودعمها وبیعها للمستهلك باسعار مخفضة، حیث ان سعرها عندما یكون اقل من المستورد سیلجأ المستهلك الى ش ا رئها بالتأكید، فضلا عن خفض قیمة الرسوم والض ا رئب على استی ا رد المواد الخام الداخلة بالصناعة. ٣٤ Abstract The policy of dumping local markets with imported products, which increased in order annually since 2003 up to date without any effective intervention or establishment of rules which is organizing the processes to import commodities- which does not find whom deters or make it subjects to the worked minimum rules of inspection, standardization and quality control that Iraq was already dealt with at minimum prior to 2003- extended to become permanent contrary to what expected that it would become an episodic event extending to limited. Thus, with a passing of time, this became as dilemma requiring rooted resolutions. In spite of all obstacles which manufacturers persevered to deal with and bear its effects, rather than the minimum profits earned by local manufactured product which rarely to find a demand in the markets by several customers whom still they have confidence in Iraqi products and purchased them occasionally, some circumstances contributed greatly to exacerbate the phenomenon of commodity dumping such as decreasing of governmental support to the national industry because of the reported trends in directing towards market economies and the privatization of governmental sector without study, planning, and passing in a transitional phase for limited time period through the direction from an economy that is depended on a government to the economy that is opened to the market system and private sector. Commodity dumping policy is one that has a critical effects or dimensions on the Iraqi economy for many reasons including that the cheap and bad commodities remove the good ones from the competition in the local market. So that, the state should prioritized its tasks currently to be included with a long and short terms work plans and programs to put limit for that by activating the role of the standardization and quality control and importing new equipment that is specialized with inspection of imported commodities and designating an efficient staff to work them, and steering to establish laws and rules that is limiting the commodity dumping phenomenon and organizing the exportimport processes, as well as the necessity of supporting the national industry through providing the encouragement by the state to the companies and institutions and purchasing their commodities and supporting and selling them to the consumer in a low prices , since its lower price than the imported one will certainly push the consumer to buy it, rather than the low value of taxes and customs which is imposed on the import of row materials used in the industry.